Waste to energy for small cities: Economics versus carbon footprint - Ng, Wendy; Varbanov, P.; Klemeš, J.; Hegyháti, M.; Bertók, B.; Heckl, I.; Lam, H. (2013)
The main activities in Waste to Energy processing include waste generation, collection, separation, transportation, conversion, energy distribution, and ultimate waste disposal. Waste to Energy carries a trade-off between energy generation and the energy spent on collection, transport and treatment. Major performance indicators are cost, Waste Energy Potential Utilisation, and Carbon Footprint. This presentation analyses the potential of small cities to substitute part of their fossil fuels use by energy derived from Municipal Solid Waste. Several factors are considered in the study. The impact of waste logistics and the losses from energy distribution systems - natural gas pipeline and electricity grid are the most significant ones on the side of the supply chain. Further, the waste processing part, including the energy recovery from the waste involves the evaluation of a number of technologies linked with each other to form a distributed integrated processing system. In this study, the options for converting waste into thermal energy include (a) biogas digestion and burning and (b) waste incineration with off-gas cleaning. It is also possible to use the biogas in advanced cogeneration systems based on engines or fuel cells. The proposed procedure takes all these options into account and derives the optimal processing configuration from the waste generation to energy supply and residual waste deposition to landfill.